2016
DOI: 10.3390/polym8030094
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Mechanical Behavior of Silk Fibroin Reinforced Waterborne Polyurethane

Abstract: Waterborne polyurethane (WPU) is a versatile and environment-friendly material with growing applications in both industry and academia. Silk fibroin (SF) is an attractive material known for its structural, biological and hemocompatible properties. The SF reinforced waterborne polyurethane (WPU) is a promising scaffold material for tissue engineering applications. In this work, we report synthesis and characterization of a novel nanocomposite using SF reinforced WPU. The rheological behaviors of WPU and WPU-SF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…The absorption band at 1720–1730 cm −1 (C=O stretching vibration) and 1591 cm −1 (benzene ring stretching) are characteristic peaks of polyurethane. Any specific interactions such as strong hydrogen bonding between PU and silk fibroin will result in peak shift or new peak [ 25 , 26 ]. However, the spectra obtained for the 100% PU and PU/RSF blends do not show any peak shift or presence of new peak in this region and suggests that no specific interactions between PU and RSF content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption band at 1720–1730 cm −1 (C=O stretching vibration) and 1591 cm −1 (benzene ring stretching) are characteristic peaks of polyurethane. Any specific interactions such as strong hydrogen bonding between PU and silk fibroin will result in peak shift or new peak [ 25 , 26 ]. However, the spectra obtained for the 100% PU and PU/RSF blends do not show any peak shift or presence of new peak in this region and suggests that no specific interactions between PU and RSF content.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are several examples on PU and silk fibroin composite films [ 22 , 25 , 26 , 27 , 28 ], fibre [ 29 ] and hydrogels [ 30 ] based on physical blending and chemical modification methods. However, rare study is reported on the preparation of biomimetic Polyurethane/Regenerated silk fibroin (PU/RSF) composite fibres possessing egg case-silk-like mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report a novel application of black phosphorene as a flame retardant for polymers. We choose waterborne polyurethanes (WPU) as the matrix polymer since WPU have been widely used in the films, adhesives, paints, varnishes, and coatings, but they are inflammable, leading to an non-negligible disadvantages that threatens people’s safety [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…With an increase in the porphyrin concentration, the storage modulus also increased, resulting in a higher value of S (Table ). Low values of n indicate a purely elastic gel behavior …”
Section: Resultsmentioning
confidence: 99%